Geochemical and hydrogeochemical characteristics and evolution of Kozaklı geothermal fluids, Central Anatolia, Turkey. (July 2019) - Şener, Mehmet Furkan; Baba, Alper
Highlights: Kozaklı shallow cold spring waters are mostly of Ca-Na-HCO3 and Ca-Mg-HCO3 type, whereas deep geothermal fluid are Na-Ca-Cl-SO4 type. The δ 18 O and δ 2 H values of thermal waters indicate their deep-circulating and high-altitude meteoric origin. REY anomalies are inheritance from geologic host materials and/or fractionation of these elements during water-rock interactions. Kozaklı is suitable for geothermal system and geothermal potential reaches its maximum level at the intersections of volcanism and tectonism. Abstract: Kozaklı is one of the most important areas of Central Anatolia in terms of geothermal potential and it is characterized by thrust and normal faults. These faults, accommodating deep circulation of hydrothermal fluids of meteoric origin, are the primary controls of the geothermal systems in this region. Chemical and isotopic composition of the hot springs and geothermal fluids was monitored throughout 2017. The surface temperature of the fluid ranges from 24.9 to 96 °C. The cold spring waters are mostly of the Ca-Mg−HCO3 type in the study area. Major element chemistry of the water reveals that the deep geothermal fluids are mostly of the Na-Ca-Cl-SO4 type while the shallow geothermal well waters are Ca-Na−HCO3 waters. Silica geothermometers suggest that the reservoir temperature ranges from 103 to 173 °C. Based on the δ 18 O– δ D relationship, water samples have a high-altitude meteoric origin. Stable isotopic data indicate that the geothermal fluids are formed by local recharge and deep circulation of meteoric waters. The Rare Earth Elements and Yttrium (REY) composition showed that Eu, Ce and Y anomalies are related both to inheritance from geological host materials and the fractionation of these elements during water-rock interactions.